INTERREGIONAL INTERACTION IN TERMINAL CLASSIC YUCATAN: RECENT OBSIDIAN AND CERAMIC DATA FROM VISTA ALEGRE, QUINTANA ROO, MEXICO. Issue 3 (21st June 2018) - Glover, Jeffrey B.; Hruby, Zachary X.; Rissolo, Dominique; Ball, Joseph W.; Glascock, Michael D.; Shackley, M. Steven
Abstract : We use ceramic and obsidian data from the ancient Maya port site of Vista Alegre to discuss long-distance exchange during the Terminal Classic (c. AD 850–1100) period. This is a time often associated with increased international trade relations and the growth of Chichen Itza as a dominant regional power in the northern Maya lowlands. Critical to the increased volume of international trade were the merchants who transported goods along the coast of Yucatan in large trading canoes. By combining a macroscopic assessment of the ceramics with visual, XRF, and INAA analyses of the obsidian artifacts, we gain insight into the various socioeconomic forces at work moving goods around the Peninsula. Given the paucity of Terminal Classic settlement in the interior Yalahau region, Vista Alegre appears to be an isolated site during this period, approximately 40 km from the nearest coastal neighbor. This allows us to focus on coastal exchange as the sole means by which goods arrived at the site. Our preliminary data contribute to the growing literature on the role market economies played in the Maya area, and the increased opportunities this afforded coastal peoples as circum-peninsular trade became more common through time. Abstract : En este trabajo utilizamos información sobre la cerámica y la obsidiana del antiguo puerto Maya de Vista Alegre, Quintana Roo, México, para discutir el intercambio a larga distancia durante el periodo Clásico terminal (ca. 850–1100 dC). Dicho periodo es frecuentemente asociado con el incremento de las relaciones comerciales internacionales y el crecimiento de Chichén Itzá como centro regional dominante en las tierras bajas Mayas del norte. Los comerciantes que transportaban bienes a lo largo de la costa de Yucatán en grandes canoas comerciales fueron fundamentales para el aumento del volumen del comercio internacional. Combinando la examinación macroscópica de la cerámica con el estudio visual, por fluorescencia de rayos X y por análisis instrumental de activación neutrónica (XRF e INAA, respectivamente, por sus siglas en inglés) de los artefactos de obsidiana, se obtuvo información sobre las diversas fuerzas socio-económicas involucradas en el transporte de mercancías alrededor de la península. Dada la escasez de asentamientos del Clásico terminal en el interior de la región de Yalahau, Vista Alegre parece haber sido un sitio aislado durante este periodo, localizado a aproximadamente 40 km del asentamiento costero más cercano. Esto permite enfocarnos en el intercambio costero como el único medio por el cual las mercancías llegaron al sitio. La información preliminar aquí presentada contribuye al creciente conjunto de investigaciones sobre el papel que desempeñaron las economías de mercado en el área Maya y las mayores oportunidades que esto brindó a los pueblos costeros.